1 William W. Mansfield, A Digest of the Statutes of Arkansas: Embracing All Laws of a General and Permanent Character in Force at the Close of the Session of the General Assembly of One Thousand Eight Hundred and Eighty-Three 490, § 1909 (1884) - (:unkn) unknown (My University, 1884)
Prohibited the sale, barter, exchange, disposal or furnishing, or keeps any dirk, Bowie-knife, sword or spear in a cane, brass or metal knuckles, or any kind of pistol or cartridge. Violators guilty of a misdemeanor.
Keywords: TRANSFER & POSSESSION